THE RELATION OF INSTITUTIONALIZED RELIGION AND RACISM IN VIDEO GAME DRAGON AGE ORIGINS (2009) - Thara Nadhifa Zakirah (HISKI, 2022)
The exponential growth of video games in popular culture has been piquing scholars' attention for years. Video games are unique compared to other media as they provide interactive experience for the users by giving them the power to choose. It has been argued that mythologies and belief systems play an important role in video games, wherein they act as referents to which video games are based on. This study aims to research how the major belief system in Dragon Age: Origins (2009) is interconnected with the in-game racial hierarchy. Using textual analysis as the method, the game narrative and mechanics are studied in order to pinpoint the connection between institutionalized religion and racism. The findings show that there are complex relations between racism and institutionalized religion. Through time, the study of religious racism and our understanding of religiosity evolved. Although there is no explicit positive correlation between the two, it is not entirely unrelated either. We must be careful not to oppose religion itself, but to criticize the other dynamics that come into play such as power and money.AbstrakPertumbuhan pesat gim video dalam budaya populer telah menarik perhatian cendekiawan selama bertahun-tahun. Gim video adalah media yang unik karena pemain mendapatkan kuasa untuk memilih, membuat gim video menjadi media interaktif. Keberadaan mitologi dan sistem kepercayaan dipercaya sebagai pemegang peran penting dalam gim, yang mana kedua hal tersebut menjadi referensi yang menjadi dasar dari gim secara umum. Studi ini bertujuan untuk meneliti bagaimana keyakinan mayoritas dalam gim Dragon Age: Origins (2009) saling berhubungan dengan hierarki ras yang ada dalam gim tersebut. Metode yang diambil adalah analisis tekstual yang mana narasi dan mekanisme dalam gim dipelajari guna menunjukkan hubungan antara lembaga agama dan rasisme. Hasil penelitian menunjukkan adanya hubungan kompleks di antara rasisme dan lembaga agama. Seiring dengan berjalannya waktu, studi tentang rasisme agama dan pemahaman kita akan religiusitas terus berkembang. Meskipun tidak ada relasi yang absolut di antara rasisme dan lembaga agama, tidak bisa dipungkiri bahwa keduanya sama sekali tidak terikat satu sama lain. Kita harus berhati-hati untuk tidak menentang agama, melainkan mengkritik faktor-faktor lain yang ikut berperan seperti uang dan kekuasaan.